An Uncommon Association of Familial Partial Lipodystrophy, Dilated Cardiomyopathy, and Conduction System Disease. (July 2016) - Panikkath, Ragesh; Panikkath, Deepa; Sanchez-Iglesias, S.; Araujo-Vilar, D; Lado-Abeal, Joaquin
A 46-year-old African American woman presented with severe respiratory distress requiring intubation and was diagnosed with nonischemic cardiomyopathy. She had the typical phenotype of familial partial lipodystrophy 2 (FPLD2). Sequence analysis of LMNA gene showed a heterozygous missense mutation at exon 8 (c.1444C>T) causing amino acid change, p.R482W. She later developed severe coronary artery disease requiring multiple percutaneous coronary interventions and coronary artery bypass surgery. She was later diagnosed with diabetes, primary hyperparathyroidism, and euthyroid multinodular goiter. She had sinus nodal and atrioventricular nodal disease and had an implantable cardioverter defibrillator implantation due to persistent left ventricular dysfunction. The device eroded through the skin few months after implantation and needed a re-implant on the contralateral side. She had atrial flutter requiring ablation. This patient with FPLD2 had most of the reported cardiac complications of FPLD2. This case is presented to improve the awareness of the presentation of this disease among cardiologists and internists.